Flexible transparent electrode and preparation method and application thereof

By forming a flexible transparent electrode with a dielectric layer/metal/dielectric layer structure on a flexible substrate, the problems of high brittleness, high cost and low light transmittance under bending stress are solved, and the effects of high conductivity, low absorption and high light transmittance are achieved.

CN119811752APending Publication Date: 2025-04-11NANJING UNIV OF POSTS & TELECOMM
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510027647.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing flexible transparent electrode materials have high mechanical brittleness, high cost and low light transmittance under repeated bending stress, making it difficult to meet the needs of flexible optoelectronic devices.

Method used

A flexible transparent electrode with a dielectric layer/metal/dielectric layer structure is used to form a uniform and dense nano-scale metal film by evaporating anti-reflective material, an amino-containing polymer solution and a metal layer on a flexible substrate, and a light transmission-regulating microcavity structure is formed through the dielectric layer.

Benefits of technology

It achieves high conductivity, low absorption, good mechanical stability and high light transmittance. The light transmittance of the composite electrode can reach more than 90%, and the square resistance is less than 10Ω/sq, which is suitable for large-area manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119811752A_ABST
    Figure CN119811752A_ABST
Patent Text Reader

Abstract

The invention provides a flexible transparent electrode and a preparation method and application thereof, and belongs to the technical field of flexible electronics, and the flexible transparent electrode is composed of a flexible, transparent and bendable substrate, a dielectric layer I, an anchoring layer, a metal layer and a dielectric layer II from bottom to top. The dielectric layer I and the dielectric layer II are made of an anti-reflection material, and the anchoring layer is made of an amino-containing polymer solution. The preparation method comprises the following steps: firstly evaporating an anti-reflection material on a flexible, transparent and bendable substrate to serve as a dielectric layer I, then spin-coating an amino-containing polymer solution to serve as an anchoring layer, and then sequentially evaporating metal to serve as a metal layer and evaporating the anti-reflection material to serve as a dielectric layer II. According to the flexible transparent electrode, through the nucleation induction effect of the anchoring layer, uniform, compact and communicated nanoscale metal is formed, the conductivity is remarkably improved, and good light transmission is guaranteed. The light transmittance of the electrode can reach more than 90%, the sheet resistance is lower than 10 omega / sq, and the electrode also has good mechanical stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of flexible electronic technology, and in particular relates to a flexible transparent electrode with a dielectric layer / metal / dielectric layer structure and a preparation method and application thereof. Background Art

[0002] In the past few decades, as human beings have been exploring various fields (transportation, biomedicine, consumer electronics, sports, clean energy and environment) in depth, flexible optoelectronic devices have been born. The emergence of flexible optoelectronic devices has made wearable consumer electronics a reality, and has therefore attracted widespread attention from the scientific research community and the industry. Among them, flexible transparent electrodes, as key components of flexible optoelectronic devices, play a very important role. At present, transparent electrodes based on transparent conductive oxides (such as indium tin oxide, ITO) are widely used in various optoelectronic devices due to their low resistivity and high transmittance in visible light. However, due to their high price, inherent mechanical brittleness under repeated bending stress and small bending radius, they have serious weaknesses in realizing flexible electronic products. Although many new flexible transparent electrode materials have been developed in the past 20 years to solve these problems, such as metal grids, metal nanowires, graphene, carbon nanotubes, conductive polymers, etc., most flexible transparent electrodes face various defects and deficiencies of their own and still cannot meet the needs of flexible optoelectronic devices. Therefore, we need to find a new transparent electrode that has high transmittance, good conductivity, good flexibility, simple preparation process and cheap materials to replace the ITO electrode.

[0003] The development of nanometal electrodes is considered to be an effective way to achieve high-performance, large-area flexible transparent electrodes. These electrodes have excellent transmittance, electrical conductivity and mechanical flexibility. In addition, one of the significant advantages is that they can use mature and easy-to-control thermal evaporation systems. However, due to the mismatch between the surface energy of flexible substrate materials and metals, it is difficult to directly form continuous ultrathin nanometal films on flexible substrates. The metal droplets evaporated onto the substrate migrate and aggregate disorderly to form a discrete particle morphology containing many irregular islands with a film thickness of less than 10nm. As the film thickness increases beyond about 15nm, the metal islands connect to each other and form a continuous metal film with low square resistance, but as the thickness of the metal film increases, the transmittance of the electrode is greatly reduced. Therefore, how to achieve ultrathin metal electrodes with both high conductivity and high transmittance is a huge challenge. Summary of the invention

[0004] The object of the present invention is to provide a flexible transparent electrode with excellent resistivity, high light transmittance, good flexibility, simple process, and large-area manufacturing, as well as a preparation method and application thereof.

[0005] The technical solution adopted by the present invention is as follows:

[0006] A flexible transparent electrode consists of a flexible, transparent and bendable substrate, a dielectric layer I, an anchoring layer, a metal layer and a dielectric layer II from bottom to top.

[0007] As a preferred embodiment of the present invention, the materials of the dielectric layer I and the dielectric layer II are anti-reflective materials, and the anchoring layer material is an amino-containing polymer solution.

[0008] As a preferred embodiment of the present invention, the material of the substrate is any one of polyurethane-2-amino-4-hydroxy-6-methylpyrimidine (PU-Upy), polydimethylsiloxane (PDMS), hydrogenated styrene-butadiene block copolymer (SEBS), polyacrylamide gel (PAM), polyacrylic acid gel (PAA), and polyethylene terephthalate (PET).

[0009] As a preferred embodiment of the present invention, the amino-containing polymer solution is any one of polyethyleneimine (PEI), polyvinylpyrrolidone (PVP), and polymethacrylate (PMMA).

[0010] As a preferred embodiment of the present invention, the vapor-deposited metal is any one of silver (Ag), gold (Au), and copper (Cu).

[0011] As a preferred embodiment of the present invention, the anti-reflection material is tungsten oxide (WO 3 ), molybdenum oxide (MoO 3 ), nickel oxide (NiOx), titanium oxide (TiO 2 )

[0012] As a preferred embodiment of the present invention, the thickness of the metal layer is 5nm-10nm, the thickness of the dielectric layer I and the dielectric layer II are both 20nm-50nm, the thickness of the anchor layer is 3-5nm, and the thickness of the substrate is both 300μm-500μm.

[0013] The present invention also provides a method for preparing the above flexible transparent electrode, which is one or more of scraping, spin coating, screen printing, inkjet printing, 3D printing, and vacuum evaporation.

[0014] As a preferred embodiment of the present invention, the preparation method is: firstly vapor-deposit an anti-reflection material as a dielectric layer I on a flexible, transparent and bendable substrate, then spin-coat an amino-containing polymer solution as an anchoring layer, and then successively vapor-deposit a metal as a metal layer and vapor-deposit an anti-reflection material as a dielectric layer II.

[0015] As a preferred embodiment of the present invention, the specific steps of the preparation method are:

[0016] S1. Remove the protective film on the surface of the flexible substrate, and clean the substrate ultrasonically with acetone, ethanol, and ultrapure water in sequence. 2 Blow dry the base to keep it clean;

[0017] S2, treating the substrate with ultraviolet ozone;

[0018] S3, evaporating an anti-reflection material on the substrate as a dielectric layer I; the specific steps of S3 are as follows:

[0019] The treated substrate was transferred to the thermal evaporation chamber and fixed on the sample stage with the front side facing downward. Anti-reflection material was added to the evaporation boat and the door was closed to form a closed chamber. The cold water circulation system and mechanical pump of the vacuum evaporation device were turned on to evacuate the closed chamber until the vacuum degree was less than 1×10 -3 Pa; when the pressure in the chamber reaches the required value, the evaporation boat is heated for evaporation. The evaporation current is 40A-80A and the evaporation speed is The evaporation time is 60 to 80 minutes, and the thickness of the dielectric layer I is 20 nm to 50 nm. After the evaporation is completed, the vacuum valve is closed, the air is released into the chamber through the vent valve, and then the door is opened to take out the evaporated sample.

[0020] S4, subjecting the substrate treated in S3 to ultraviolet ozone treatment, spin coating an amino-containing polymer solution on the surface of the dielectric layer I, and performing annealing treatment to form an anchoring layer.

[0021] S5, evaporating metal on the anchoring layer as a metal layer; the specific steps of S5 are:

[0022] Open the cold water circulation system of the vacuum evaporation device, fix the flexible substrate with its front side facing down on the sample stage, place the metal target in the evaporation boat, close the door to form a closed chamber, and evacuate the closed chamber until the vacuum degree is less than 1×10 -3 Pa. When the pressure in the chamber reaches the required value, the evaporation boat is heated for evaporation. The evaporation current is 25A-40A and the evaporation speed is The evaporation time is 2 to 5 minutes, and the thickness of the metal layer is 5nm-10nm; after the evaporation is completed, close the vacuum valve, release the air into the chamber through the vent valve, then open the hatch and take out the evaporated sample; this step uses vacuum evaporation technology to complete the metal coating process in a closed environment, without the use of chemical reagents or other additional operations, so the preparation process is more environmentally friendly, convenient and fast. In addition, introducing vacuum evaporation into the process of preparing ultra-thin metal films is also beneficial to improving the quality of coating and making the coating process highly controllable. The above-mentioned metal target material can be gold, silver or copper, and the purity of the target material must reach 99.99%.

[0023] S6, an anti-reflective material as a dielectric layer II on the metal layer;

[0024] The dielectric layer II is further evaporated on the surface of the metal layer prepared in step S5 by an evaporation method. The cold water circulation system of the vacuum evaporation device is turned on, the metal film of S5 is fixed on the sample stage with the front side facing downward, the anti-reflection material is placed in the evaporation boat as the target material, and the hatch is closed to form a closed chamber; the closed chamber is evacuated until the vacuum degree is less than 1×10 -3 Pa; when the pressure in the chamber reaches the required value, the evaporation boat is heated for evaporation. The evaporation current is 40A-80A and the evaporation speed is The evaporation time is 60 to 80 minutes, and the thickness of the dielectric layer II is 20nm-50nm. After the evaporation is completed, the vacuum valve is closed, and the air is released into the chamber through the vent valve, and then the door is opened to take out the evaporated sample. Finally, a flexible transparent electrode with a dielectric layer / metal / dielectric layer structure is obtained.

[0025] The anti-reflection material is an inorganic hole transport layer material, which can form the anti-reflection layer of the transparent electrode and can also be directly used as the hole transport layer of the optoelectronic device. 3 , WO 3 Or NiOx can be used, and the purity of the target material must reach 99.99%.

[0026] As a preferred embodiment of the present invention, the cleaning time of each ultrasonic cleaning in S1 is 15 to 20 minutes.

[0027] As a preferred embodiment of the present invention, the ultraviolet ozone treatment time in S2 is 15 to 20 minutes.

[0028] As a preferred embodiment of the present invention, the spin coating conditions in S4 are: the rotation speed is controlled to be 3000 rpm to 5000 rpm, and the spin coating is performed on the surface of the flexible substrate for 20s to 30s; and the annealing conditions are: annealing at 100° C. for 20 min.

[0029] The flexible transparent electrode of the present invention can be used in photoelectric devices such as flexible organic light emitting diodes, flexible solar cells, flexible transistors and flexible energy storage devices.

[0030] Beneficial effects:

[0031] (1) The ultra-thin metal flexible transparent electrode prepared by the present invention has excellent performance.

[0032] The flexible transparent electrode provided by the present invention evaporates a metal with good conductivity and ductility and low absorption of visible light on a flexible substrate, and forms a uniform, dense and interconnected nanoscale metal film through the nucleation induction effect of the anchoring layer, which significantly improves the conductivity and ensures good light transmittance. With the help of dielectric layer I and dielectric layer II, a light transmission regulation microcavity structure is formed, which suppresses total internal reflection and further improves light transmittance. The transmittance of the composite electrode can reach more than 90%, the square resistance is lower than 10Ω / sq, and the electrode also has good mechanical stability, which effectively overcomes the defects of traditional oxide transparent conductive materials with high brittleness and significant degradation of their optoelectronic properties in a bent state. It can be seen that the flexible transparent electrode with a multi-layer composite structure of the present invention has great potential in the application of flexible electrodes.

[0033] (2) The preparation method of the present invention requires few chemical reagents, has low cost, can be produced on a large scale, and the preparation process is highly controllable and simple and easy to carry out. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a schematic diagram of the structure of the flexible transparent electrode of the dielectric layer / metal / dielectric layer structure of the present invention, wherein from bottom to top are 1-substrate, 2-dielectric layer I, 3-anchoring layer, 4-metal layer, and 5-dielectric layer II.

[0035] Figure 2 These are transmission diagrams of the flexible transparent electrodes prepared in Example 1, Example 2, and Example 3 at different wavelengths.

[0036] Figure 3 The diagrams showing the changes in square resistance and transmittance of the flexible transparent electrodes prepared in Example 1, Example 2, and Example 3.

[0037] Figure 4 This is a comparison chart of the square resistance of the flexible transparent electrodes prepared in Example 1, Example 2, and Example 3 after bending.

[0038] Figure 5 The square resistance curves of the flexible transparent electrodes prepared in Example 1, Example 2 and Example 3 after the 3M tape is peeled off. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is described in detail below through embodiments, but the protection scope of the present invention is not limited to the embodiments.

[0040] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0041] Embodiment 1

[0042] A flexible transparent electrode, using thermal evaporation coating equipment as a means of growing ultra-thin films (metal layers) and anti-reflection layers (two dielectric layers). A dielectric layer is first evaporated on the flexible transparent substrate PET, and a PEI solution is spin-coated. After annealing, an anchoring layer is formed. Then, a layer of Ag is evaporated as an ultra-thin metal layer, and then a dielectric layer is evaporated to prepare an ultra-thin metal flexible transparent electrode. The bottom-up structure is PET / MoO 3 / PEI / Ag / MoO 3 , the specific preparation method is:

[0043] S1. Remove the surface protective film of a PET film with a length and width of 4 cm and a thickness of 3 mm, and ultrasonically clean the substrate with acetone, ethanol, and ultrapure water in turn for 15 min. After cleaning, use N 2 Blow dry the base to keep it clean.

[0044] S2, treating the substrate with ultraviolet ozone for 15 minutes;

[0045] S3. Transfer the treated PET to the thermal evaporation chamber and fix it on the sample stage with the front side facing downward. Add MoO 3 , close the hatch to form a closed chamber. Turn on the cold water circulation system and mechanical pump of the vacuum evaporation device to evacuate the closed chamber until the vacuum degree is less than 4×10 -4 Pa. After the pressure in the chamber reaches the required value, the evaporation boat is heated for evaporation. The evaporation current is 46A and the evaporation speed is about The evaporation time is about 60 minutes, MoO 3 The thickness is 35nm. After the evaporation is completed, turn off the evaporation boat current, close the vacuum valve and the molecular pump. After the molecular pump stops, release the air through the vent valve, then open the cabin door and take out the evaporated sample.

[0046] S4, spin coating a 4% PEI solution on the treated flexible substrate surface, and then annealing at 100° C. for 20 min;

[0047] S5. Ag is evaporated as an ultra-thin metal layer on the spin-coated PEI substrate by evaporation. The evaporation current is 28A and the evaporation speed is The evaporation time is 2 min and the thickness of the metal film is 6 nm.

[0048] S6, evaporate MoO on the basis of S5 3 A dielectric layer is deposited to form an ultra-thin metal flexible transparent electrode with a multi-layer structure, wherein the evaporation method used is the same as that of S3.

[0049] Example 2

[0050] A flexible transparent electrode, using thermal evaporation coating equipment as a means of growing ultra-thin films and anti-reflection layers. From bottom to top: PET / WO 3 / PEI / Ag / WO 3 , where WO is evaporated 3 When the evaporation current is 80A, the evaporation rate is The evaporation time is 60 min, the thickness is 35 nm, and the other parameters are the same as those in Example 1.

[0051] Example 3

[0052] A flexible transparent electrode that uses thermal evaporation coating equipment as a means of growing ultra-thin films and anti-reflection layers. The bottom-up structure is PET / WO 3 / PEI / Ag / MoO 3 , other parameters are the same as those in Examples 1 and 2.

[0053] Figure 2 These are transmission diagrams of the flexible transparent electrodes prepared in Example 1, Example 2, and Example 3 at different wavelengths. Figure 3 The sheet resistance and transmittance change diagrams of the flexible transparent electrodes prepared in Example 1, Example 2, and Example 3 are shown in Table 1:

[0054] Table 1

[0055]

[0056] At the same time, the electrode prepared in the above embodiment also has good mechanical stability. Figure 4 It can be seen that the square resistance of the electrode does not change much after bending 2000 times with a bending radius of 2 mm. In contrast, the square resistance of the ITO transparent electrode increases sharply after bending, indicating that the electrode of the present invention has excellent bending resistance. In addition, the electrode is peeled off using 3M tape. Figure 5 It can be seen that the electrode square resistance still maintains a low value after 20 peelings, which proves that the anchoring effect of the amino-containing polymer solution is very strong and the metal droplets are firmly fixed on the substrate surface.

[0057] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes may be made to the form and details without departing from the spirit and scope of the present invention.

Claims

1. A flexible transparent electrode, characterized in that: The flexible transparent electrode consists of a flexible, transparent and bendable substrate, a dielectric layer I, an anchoring layer, a metal layer and a dielectric layer II from bottom to top.

2. The flexible transparent electrode according to claim 1, characterized in that: The materials of the dielectric layer I and the dielectric layer II are anti-reflection materials, and the material of the anchoring layer is a polymer solution containing amino groups.

3. The flexible transparent electrode according to claim 2, characterized in that: The amino-containing polymer solution is any one of polyethyleneimine, polyvinyl pyrrolidone, and polymethacrylate; The anti-reflection material is any one of tungsten oxide, molybdenum oxide, nickel oxide, and titanium oxide; The material of the substrate is any one of polyurethane-2-amino-4-hydroxy-6-methylpyrimidine, polydimethylsiloxane, hydrogenated styrene-butadiene block copolymer, polyacrylamide gel, and polyacrylic acid gel; The metal is any one of silver, gold and copper.

4. The flexible transparent electrode according to claim 1, characterized in that: The thickness of the metal layer is 5nm-10nm, and the thickness of the dielectric layer I and the dielectric layer II are both 20nm-50nm.

5. The method for preparing a flexible transparent electrode according to any one of claims 1 to 4, characterized in that: The preparation method is one or more of blade coating, spin coating, screen printing, inkjet printing, 3D printing, and vacuum evaporation.

6. The method for preparing the flexible transparent electrode according to claim 5, characterized in that: The preparation method is: On a flexible, transparent and bendable substrate, an anti-reflection material is first evaporated as a dielectric layer I, and then an amino-containing polymer solution is spin-coated as an anchoring layer, and then metal is evaporated in sequence as a metal layer and an anti-reflection material is evaporated as a dielectric layer II.

7. The method for preparing a flexible transparent electrode according to claim 6, characterized in that: The steps include: S1, tear off the surface protective film of the flexible substrate, ultrasonically clean the substrate with acetone, ethanol, and ultrapure water in sequence, and blow dry with N2; S2, treating the substrate with ultraviolet ozone; S3, evaporating an anti-reflection material on the substrate as a dielectric layer I, the evaporation conditions are: evaporation current 40A-80A, evaporation speed The evaporation time is 60 to 80 minutes; S4, after the substrate treated in S3 is subjected to ultraviolet ozone treatment, a polymer solution containing amino groups is spin-coated on the surface of the dielectric layer I, and annealing is performed to form an anchoring layer; S5. Deposit metal on the anchor layer as a metal layer. The deposition conditions are: deposition current 25A-40A, deposition speed The evaporation time is 2 to 5 minutes; S6. Anti-reflection material is used as dielectric layer II on the metal layer. The evaporation conditions are: evaporation current 40A-80A, evaporation speed The evaporation time is 60 to 80 minutes.

8. The method for preparing a flexible transparent electrode according to claim 7, characterized in that: The spin coating conditions in step S4 are: the rotation speed is controlled to be 3000 rpm to 5000 rpm, and the spin coating time is 20 s to 30 s; and the annealing conditions are: annealing at 100° C. for 20 min.

9. The method for preparing a flexible transparent electrode according to claim 7, characterized in that: The cleaning time of each ultrasonic cleaning in S1 is 15 to 20 minutes; the treatment time of the ultraviolet ozone treatment in S2 is 15 to 20 minutes.

10. Use of the flexible transparent electrode according to any one of claims 1 to 4 in a photoelectric device.

Citation Information

Patent Citations

  • Electrode having excellent light transmittance, method for manufacturing same, and electronic element including same

    CN105684098A

  • Composite transparent conductive film and amino acid anchoring method preparation process and application thereof

    CN114411089A

  • Chip for surface plasmon resonance sensor and surface plasmon resonance sensor

    US20100067015A1

  • Transparent substrate with conductive multilayer anti reflection film, transparent touch panel using the transparent substrate with multilayer anti reflection film and electronic apparatus using the touch panel

    US6727566B1